-
Solution: Derived from the question.
Because y-3 is directly proportional to x.
So y-3≠0, x≠0
Get: y≠3,x≠0
Let y-3 be proportional to x and t
i.e. y-3 x=t
Substituting x=2, y=7 into y-3 x=t is obtained.
t=2, so the function relation is y=2x+3
When x=4, substitute y=2x+3
Get y=11 and when y=4, substitute y=2x+3
Get x=1 2
-
Solution: Since y-3 is proportional to x, y-3=kx is obtained from y=kx.
So y=kx+3
When x=2, y=7, so k=2
So the analytic formula of the function is y=2x+3
When x=4, y=11
When y=4, x=1 2
-
You treat Y-3 as a whole.
Then it is y-3=kx
then y=kx+3
Next, you can substitute the evaluation.
Answer: y=11
, x=1 2
Presumably the answer should be correct.
-
2.Let x=, the solution is k=2, so y-3=2x, i.e., y=2x+3 let x=4, then y=11
3.Let y=4, then x=1 2
-
y-3=kx substituting x= into k=2, so the algebraic formula is y=2x+3 x=1 2
-
y-3 is proportional to x, and y-3=kx(k≠0) is proportional.
Substituting x=2 and y=7 gives 7-3=2k, k=2;
The functional relationship between y and x is: Wang Jianliang y=2x+3,
-
The so-called proportional group such as 晌 means that the oak space has y+3=k(x+2), where k>0
Replace x=3, y=7Substituting yields 7+3=k(3+2) k=2
So collapse front y = 2x+1
-
Since y-3 is proportional to x, the parameter a can be set, and y-3=ax
When x=2 and y=7, a=2
Then, the analytic formula of the function of (1) y on x is: y=2x+the range of values is negative infinity to positive infinity.
2) When x=-1, y=1
3) When y is zero, the value of x ranges from negative infinity to negative 3/2.
-
(1) Let y-3=kx
When x=2 and y=7, substitution obtains.
7-3=2k
k=2y-3=2x
y=2x+3
2) When x=-1 2, y=2x+3=-1+3=2(3) because of the translation, k does not change, let y=2x+b, and the substitution point (2,-1) gets -1=2*2+b
b=-5, so the analytic formula after translation is y=2x-5
-
Let y-3=kx
When x=2, y=7
7-3=2k
k=2y-3=2x
y=2x+3
When x=-1 2, y=2x+3=-1+3=2, draw the image yourself.
-
Solution: (1) y-3 is proportional to x, y-3=kx(k≠0) is proportional, when x=2, y=7 is substituted, 7-3=2k, k=2;
The functional relationship between y and x is: y=2x+3, 2) substituting x=-1 yields: -1x2+3=1
3.x is less than.
-
According to the question search buried state meaning:
y+3=k(x-2)
Substitute x=3 and y=7.
7+3=k(3-2)
k=10y+3=10(x-2)
y=10x-23
Positive proportionality is that the number of liquids increases in proportion to the increase of another number according to the fixed proportion.
-
(1) Because y-3 is proportional to x.
So let y - 3 = kx
So y=kx+3
Because when x = 2, y = 7
So 2k + 3 = 7
So k = 2
So y = 2x + 3
2) When x = -1 2.
y = 2×(-1/2) +3 = 2
-
(1) y-3 is proportional to x, y-3=kx(k≠0) is proportional, when x=2, y=7 is substituted into it, and 7-3=2k, k=2;
-
y+3=kx
Substituting x=2 and y=7 gets:
7+3=2k
k = 5 to get y 3 = 5x
y=5x-3
When x = 1 2, y=5 ( 1 2) 3 = 11 2 to make the translated image pass (4, 3), then: y=5x 23 [pan down 20 units].
-
y+3=kx
When x=2, y=7
7+3=2k,k=5
So y=5x-3
When x=-1 2, y=-11 2
The slope is the same after translation, which is 5
Let y=5x+b
Points (4, -3) are brought in.
20+b=-3
b=-23y=5x-23
This is a more professional question, but let me give you my opinion: >>>More
Lenovo A798T uses MTK dual-core processor with 512M RAM running memory, and the performance is mainstream. The screen uses an inch 854*480 resolution TFT screen, which has a good display effect and is equipped with a 5 million pixel camera, which can bring good photo results. >>>More
The effort is not proportional to the return. It can only be said that some things may not have come to fruition after working hard, but we still have to work hard, why is that? It may just be that we haven't seen the results for the time being, and the success of many careers actually requires three to five times the effort in the early stage compared to others. >>>More
The proportional function y=kx intersects with the parabola y=ax 2+3 at (2,4)=》2k=4 4a+3=4 >>>More
From 3x-2y=5, we get the formula that represents y by x, y=(5-3x 2). >>>More